The locus of control and its relationship to psychological anxiety among Individuals Recovering From COVID-19 in Madinah - Sagga, Roaa Talal (Journal of Educational and Psychological Sciences, 2024)
The current study examines the relationship between the level of the locus of control (internal-external) and the level of psychological anxiety of the individuals recovering from COVID-19 in Medina, which was identified in (230) of them (195) females and (35) males in order to serve the objectives of the study, the descriptive analytical correlational approach was used, and the internal-external Rotter’s locus of control scale was applied, and the Taylor scale for explicit anxiety, and the results exhibited that there is a high level of locus of control (internal), while the level of psychological anxiety of the sample members reached (Free of anxiety), and the results also exhibited in a statistically significant Inverse relationship between the internal control point and psychological anxiety, In other words, the greater the internal locus of control point, the lower the level of psychological anxiety. The study confirmed that women suffer from a high level of anxiety, and that young people (25-42) suffer more than others from psychological anxiety.